(untitled) (Annals of Medical Research, 2021)
Aim: The purpose of this study was to investigate if the grade of lumbar disc degeneration. Intervertebral disc degeneration is a common degenerative disease.Material and Methods: A retrospective analysis on 34 males and 48 females with intervertebral discs degeneration and a mean age of 51.5 years. Using MRI, the grade of lumbar intervertebral discs degeneration was assessed according to the Pfirrmann classification.Results: There was a high correlation (R =0.385) and significant association (pearson correlation, p 0.01) between L3/L4 disc degeneration and the aging. There was also a high correlation (R =0.56) and significant association (pearson correlation, p 0.001) between the L3/L4 disc degeneration and the L4/L5. Conclusion: For many years, excessive or abnormal mechanical load was thought to be the main cause of disk degeneration. Rates of aging and lumbar disc degeneration have gradually increased over the years. It is important to note that there is a significant relationship between aging and L3 / L4 disc degeneration and that L4 / L5 disc degeneration may also be present in patients with L3 / L4 disc degeneration.